Durability properties of a non-cement binder made up of pozzolans with sodium hydroxide. (1st May 2017) - Karim, M.R.; Hossain, M.M.; Zain, M.F.M.; Jamil, M.; Lai, F.C.
Highlights: Strength, water absorption and porosity of a non-cement mortar were determined. Chloride penetration, sulfate, thermal and corrosion of mortar also investigated. Non-cem was produced from slag, POFA and RHA with NaOH at 2.5 M solution. Water absorption and porosity were found as 8.1% and 16.3% respectively at 28-days. Chloride, sulfate, thermal and corrosion resistance of mortar were found well. Abstract: The durability property of a mortar is the second most important concerns next to its strength. This study investigates some durability properties of a Non-cement binder (Non-cem). The Non-cem was produced from pozzolans such as slag, palm oil fuel ash, and rice husk ash alongside a 2.5 M sodium hydroxide solution. The mortar of Non-cem was tested for its compressive strength, water absorption, porosity, chloride penetration, sulfate, corrosion, and thermal resistance (heated at 700 °C for 2 h) as well as compared to that of ordinary Portland cement (OPC) mortar. The results reveal that Non-cem mortar gains compressive strength of 42.84 MPa (93.36% of OPC) at 28 days. Water absorption and porosity at 28 days are found to be 8.1% and 16.3% for Non-cem mortar whereas 6.2% and 13.5% for OPC mortar, respectively. The chloride penetration of Non-cem and OPC mortars are found to be 11.5 mm and 10.1 mm respectively at 28 days. The sulfate resistance of Non-cem mortar is much higher than that of OPC (i.e., the reduction in compressive strength of Non-cem and OPC mortars were 12.6% and 14.1% respectively because of immersion in 5% magnesium sulfate solution after one month). In case of corrosion resistance, cracks are shown in OPC mortars earlier than Non-cem mortars and in case of thermal resistance of Non-cem mortars lose their strengths by 19.21% whereas OPC mortars lose their strengths by 32.87%. These test results indicate that Non-cem could be used as an alternative of cement.